A perspective on mental health literacy and mental health issues among Australian youth: Cultural, social, and environmental evidence! - Bennett, Hirukshi; Allitt, Ben; Hanna, Fahad (Frontiers in Public Health, 2023)
Mental health literacy (MHL) helps improve mental health outcomes and reduce the impacts of mental illness. This study aims to review scientific evidence in relation to mental health literacy levels and their impacts on mental health among Australian youth. The factors explored in the Perspective included; influence of social determinants, culturally and linguistically diverse (CALD) communities, help-seeking attitudes and behaviours. MHL intervention programs and MHL for improving mental health outcomes due to the recent covid-19 pandemic were also explored. Adequate levels of youth mental health literacy significantly improved one’s ability to recognise own mental health status as well as provide peer support. Practical considerations such as designing more gender and culturally specific youth mental health literacy programs are proposed.